Development of Industry-Based Occupational Safety and Health Learning Aids for Automotive Vocational School Students - Bambang Sudarsono; Wegig Pratama (Universitas Sultan Ageng Tirtayasa, 2024)
Occupational Safety and Health (K3) is an important aspect for creating a safe and healthy work environment. K3 is a competency that all prospective workers, especially vocational school graduates, must have. K3 learning tools are needed that play an important role in presenting industry-based knowledge, as well as emphasizing K3 practices in an interactive and interesting way in learning. This research aims to develop K3 learning teaching aids and test their effectiveness in improving student competence. This research is research and development (R&D) which adopts the Four-D development model consisting of Define, Design, Develop, and Disseminate. The object of the research was carried out at SMK Muhammadiyah 2 Sleman with the research subjects consisting of 34 students, 2 teachers and 2 industrial practitioners. Data collection techniques use tests and non-tests with research instruments in the form of interviews, questionnaires and practical performance tests. The development of industry-based K3 teaching aids was carried out well and effectively increased K3 competency during two trials. The achievement of K3 competency can be seen from the increase in the average score of the competency test in the limited trial stage with a score of 68 and the score in the expanded trial of 88.